Monitoring intra‐abdominal pressure after liver transplantation in children. (31st August 2019) - Deindl, Philipp; Wagner, Jula; Herden, Uta; Schulz‐Jürgensen, Sebastian; Schild, Raphael; Vettorazzi, Eik; Bergers, Marlies; Keck, Maike; Singer, Dominique; Fischer, Lutz; Herrmann, Jochen
Abstract: IAH after LTX can impair perfusion and threaten graft viability. This study aimed to assess the feasibility of longitudinal IAP measurements as an IAH screening method in children after LTX. A cohort of 23 children with a mean age (range) 3.1 (3 months–14 years) who underwent LTX between May 2017 and February 2018 were evaluated retrospectively. Longitudinal IAP measurements were compared to bedside Doppler US monitoring data. In total, 425 IAP measurements and 257 US examinations were performed. The mean ± SD (range) time expenditure for IAP measurement was 1.9 ± 0.4 (0.5‐3.2) minutes. The mean post‐operative IAP was 7.9 ± 3.6 (1‐25) mm Hg. IAH (IAP ≥ 10 mm Hg) was noted in 102 (24%) of 257 measurements. Agitation had a significant impact on IAP (estimate: 9.3 mm Hg, CI: 6.72‐11.97, P < .01). In patients with TAC, IAP was increased (6.7 ± 2.1 vs 8.7 ± 3.1 mm Hg, P = .02) while peak portal venous velocities decreased (38 ± 27 vs 26 ± 22 cm/s, P = .03) after patch reduction. An abdominal compartment syndrome with severely impaired vascular flow was noted in one patient. Episodes of elevated IAP were noted in a large proportion of patients, underscoring the need for IAP monitoring in pediatric liver transplant recipients. The safety and low time expenditure associated with IAP measurement could be included easily into standard nursing procedures for these patients.